Knowing, Proposing and Acting: Epistemological Aspects of Medical Practice in the New Millennium. - Vargas, Rafael (Journal of Family Medicine, 2018)
In this work, it is analysed how the medical practice is imbued with Cartesian rational thought as well as empiricist thought and it is stated that medicine is an art and is science. It is proposed that the object of knowledge of the medical practice is not the concept of disease but health. It is from the concept of health and normality that medical taxonomy labels individuals as sick. This taxonomy is frequently re-evaluated and reorganized by scientific societies. This sometimes occurs according to new knowledge, but this categorization may also be questioned due to direct intervention or indirect pressure related to interests, especially economic, that are sometimes not clearly visible. Accordingly, an ongoing discussion is needed to keep the medical practice neutral against struggles of interest derived from the health industry. These topics must be considered and debated in medical schools including undergraduate and postgraduate programs.
Keywords: clinical reasoning; epistemology; health and normalcy concept; medical knowledge; medical practice; signs; symptoms